Reconceiving midwifery - Benoit, Cecilia M., 1954-; Bourgeault, Ivy Lynn, 1967-; Davis-Floyd, Robbie (Montreal, Que. : McGill-Queen's University Press, 2004)
Midwifery in the developed world is in a state of ferment and change - a phenomenon referred to as the 'new midwifery'. This title offers analysis of the new midwifery as it is practised and reflects on regional differences in the emerging profession, providing a systematic account of its historical, local and international roots and more.
Foreword / Robbie Davis-Floyd -- Introduction. Reconceiving midwifery in Canada / Ivy Lynn Bourgeault, Cecilia Benoit, and Robbie Davis-Floyd -- Rethinking the history of midwifery in Canada / Lesley Biggs -- Tradition as a political symbol in the new midwifery in Canada/ Margaret MacDonald -- Why legislation?: using regulation to strengthen midwifery / Vicki Van Wagner -- Delaying legislation: the Quebec experiment / Helene Vadeboncoeur -- Challenges to midwifery integration: interprofessional relationships in British Columbia / Jude Kornelsen and Elaine Carty -- To fund or not to fund: The Alberta decision / Susan James and Ivy Bourgeault -- Exploring legislated midwifery: texts and rulings / Mary Sharpe -- Becoming a midwife in Canada: models of midwifery education / Cecilia Benoit and Robbie Davis-Floyd -- Midwifery education in Ontario: its origins, operation, and impact on the profession / Karyn Kaufman and Bobbi Soderstrom -- Midwifery on the prairies: visionaries and realists in Manitoba / Pat Kaufert and Kris Robinson -- Unregulated midwifery: experiences of women in Nova Scotia / Denise Marion -- Access to midwifery: reflections on the Ontario Equity Committee Experience / Anne Rochon Ford and Vicki Van Wagner -- Aboriginal midwifery in Canada: merging traditional practices and modern science / Dena Carroll and Cecilia Benoit -- The Boundaries of professional belonging: how race has shaped the re-emergence of midwifery in Ontario / Sheryl Nestel -- Afterword. Missing pieces and new developments: challenges and opportunities / Ivy Lynn Bourgeault and Cecilia Benoit.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Midwifery -- Canada; Midwifery -- Canada -- History; Midwifery -- history; Canada -- midwifery; Canada; Sages-femmes -- Canada -- Histoire; Sages-femmes -- Canada; HEALTH & FITNESS -- Pregnancy & Childbirth; MEDICAL -- Gynecology & Obstetrics; Midwifery; Canada; midwives; History; Electronic books